The role of cyclic nucleotide signalling in L. mexicana flagellar motility - Fochler, S (2022)
Cyclic AMP (cAMP) is a ubiquitous conserved second messenger involved in diverse biological function across the Eukaryotic kingdom. Here we explore components of the divergent cAMP signalling pathway, including divergent protein kinase A (PKA), in the early diverging protozoan Leishmania mexicana, with an aim to understand how cAMP contributes to its canonical motile flagellum. While cAMP may transduce external signals, it is ultimately the regulation of dynein activity that determines the waveform. Therefore, we assessed the contribution of all 10 axonemal dyneins to gain a deeper understanding how each one contributes to L. mexicana waveforms. To tackle these aims, we used CRISPR-Cas9 gene deletion and endogenous fluorescent tagging combined with microscopy techniques to localise our proteins of interest and assess their contributions to flagellar wave shape and direction. We found that 24 of 35 putative cyclic nucleotide signalling components were present in the flagellum, notably in either the distal, proximal or entire axoneme. We identified cAMP at the flagellar tip serves as the main regulator of parasite swim speed. Sequence analysis, homology modelling and predicted cAMP docking suggested that only CARP1, firmly embedded in the flagellar cytoskeleton, binds cAMP via classical binding mechanisms. △CARP1 flagella demonstrated reduced beat frequencies and a higher propensity for ciliary beating. Moreover, we described the pairing preferences of PKAR1 with PKAC1/ PKAC2 in the flagellar cytoskeleton, and PKAR3 with PKAC3 to the cell body. Loss-of-function phenotypes showing distinct effects on motility with loss of PKAC1 being the most severe. Lastly, we found that the double headed axonemal dyneins were indispensable for cell displacement, however the single headed dyneins contributed more specifically to either beat frequency or amplitude. Ultimately, the findings of this thesis have systematically pinpointed the contributing components of the divergent cAMP signalling pathway to flagellar motility. What remains, is to unpick the mechanistic details of how CARP1 is interacting within its local axoneme environment to affect wave shape and direction of travel.